2020
DOI: 10.1177/0300060520909235
|View full text |Cite
|
Sign up to set email alerts
|

Jianpi Huatan Tongfu granule alleviates inflammation and improves intestinal flora in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: Objectives: To investigate the clinical efficacy and mechanism of Jianpi Huatan Tongfu granule in treating acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods: Sixty patients with AECOPD were enrolled in either of two groups: integrative treatment (Western medicine combined with Jianpi Huatan Tongfu granule) (n ¼ 30) and Western medical treatment (n ¼ 30). Thirty healthy individuals were included in the control group. Results: Compared with healthy participants, patients with AECOPD h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study revealed that gut microbiota abundance and diversity were reduced in the PIC rats, and the microbiota structure was significantly deviated from that of the normal rats, as shown by reduced abundance of Lactobacilli and Allobaculum and increased abundance of RombASVsia , Turicibacter , and unclassified_f_Oscillospiraceae . It has been reported that Lactobacilli can degrade proinflammatory chemokines to exert anti-inflammatory effects and inhibit airway inflammation and airway remodelling in asthmatic mice [ 21 ]; However, RombASVsia is considered a detrimental bacteria in the intestine that can promote inflammation, and its abundance in the intestine of rats with pneumonia is significantly increased [ 22 ]. After treatment with XBZY decoction, the gut microbiota abundance and diversity of PIC rats were significantly improved, and the microbiota structure tended to be more normal, as evidenced by increased abundance of Lactobacilli and Allobaculum with Akkermansia as the dominant genus, as well as declined RombASVsia , Turicibacter , and unclassified_f_Oscillospiraceae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that gut microbiota abundance and diversity were reduced in the PIC rats, and the microbiota structure was significantly deviated from that of the normal rats, as shown by reduced abundance of Lactobacilli and Allobaculum and increased abundance of RombASVsia , Turicibacter , and unclassified_f_Oscillospiraceae . It has been reported that Lactobacilli can degrade proinflammatory chemokines to exert anti-inflammatory effects and inhibit airway inflammation and airway remodelling in asthmatic mice [ 21 ]; However, RombASVsia is considered a detrimental bacteria in the intestine that can promote inflammation, and its abundance in the intestine of rats with pneumonia is significantly increased [ 22 ]. After treatment with XBZY decoction, the gut microbiota abundance and diversity of PIC rats were significantly improved, and the microbiota structure tended to be more normal, as evidenced by increased abundance of Lactobacilli and Allobaculum with Akkermansia as the dominant genus, as well as declined RombASVsia , Turicibacter , and unclassified_f_Oscillospiraceae .…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with XBZY decoction, the gut microbiota abundance and diversity of PIC rats were significantly improved, and the microbiota structure tended to be more normal, as evidenced by increased abundance of Lactobacilli and Allobaculum with Akkermansia as the dominant genus, as well as declined RombASVsia , Turicibacter , and unclassified_f_Oscillospiraceae . Akkermansia , a newly discovered beneficial intestinal microorganism, which can regulate intestinal barrier function and is negatively correlated with inflammation and metabolic disorder, can stimulate the host to initiate an immune response to protect against respiratory tract inflammation, thus promoting lung health [ 21 , 23 ]. Gut microbiota structure changes can directly lead to alteration in content and types of its metabolites and SCFAs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with obesity and PCOS often have spleen deficiency symptoms, such as fatigue, loss of appetite, and thin stool. In recent years, an increasing number of studies have confirmed that spleen-invigorating TCM compounds help regulate the gut microbiota and maintain intestinal microecology balance [ 24 ]. BZYQ is one of the spleen-invigorating TCM prescriptions with a remarkable impact on recovering the gut microbiota of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients with PCOS often have spleen de ciency symptoms, including obesity, fatigue, loss of appetite, and thin stool. In recent years, increasing studies have con rmed that spleen-invigorating TCM compounds help regulate the gut microbiota and maintain the balance in intestinal microecology [24]. BZYQ is one of the spleen-invigorating TCM prescriptions and have a remarkable impact on recovering the gut microbiota of the host.…”
Section: Discussionmentioning
confidence: 99%